Measuring environmental sustainability performance of South Asia. (1st April 2020) - Sun, Huaping; Mohsin, Muhammad; Alharthi, Majed; Abbas, Qaiser
Abstract: Sustainability and low-carbon economy strategies have been widely studied in the past; nevertheless, researchers often ignore the effects of combining energy, economic, and environmental factors when assessing sustainability performance. To fill this gap, we measure the environmental sustainability performance of South Asia using a common weight Data Envelopment Analysis (DEA)-like mathematical model encompassing a comprehensive, up-to-date, and relevant set of indicators. In this paper, we present a measurement of South Asia's environmental sustainability performance for the years 2001–2015. Our results reveal that Bhutan outperforms the rest of the countries in South Asia, with an overall index score of 0.72. Nepal comes second in the region, with a stable score, followed by the Maldives. Afghanistan and Bangladesh are ranked fourth and fifth, respectively, and their overall scores indicate strong potential sustainability performances. India, Sri Lanka and Pakistan follow this list, with poor scores, with Pakistan having the lowest scores during the study period. Based on these findings, we propose a policy to boost the cross-border renewable energy trade for long-term environmental sustainability. Graphical abstract: Image 1 Highlights: We select a meaningful, comprehensive, and relevant set of indicators. A DEA-like mathematical model programming approach is adopted. Measurement of South Asia's sustainability performance for 2001–2015 is addressed. Bhutan is more energy secure and environmentally sustainable in South Asian.